Parameters of the oxidative-reduction system of the homeostasis in female transplant patients with tumors of the reproductive system treated with hyperbaric oxygen therapy - A. V. Babkina; M. Sh. Khubutiya; O. A. Levina; A. K. Evseev; A. K. Shabanov; I. V. Goroncharovskaya; A. A. Medvedev (Трансплантология (Москва))
Introduction. Studies on the effects of hyperbaric oxygenation have often been represented as animal model experiments. Currently, the number of studies on the use of hyperbaric oxygen therapy in the post-transplant period in humans is growing. The need in investigating the efficacy of hyperbaric oxygen therapy in the postoperative period in female transplant patient with tumors of the reproductive system is dictated by time.The aim of the study was to evaluate the efficacy of hyperbaric oxygen therapy in the complex treatment of transplant patients at an early stage of the postoperative period.Material and methods. We have studied the course of an early postoperative period in 8 female transplant patients with reproductive system tumors treated in N.V. Sklifosovsky Research Institute for Emergency Medicine, using hyperbaric oxygenation. The hyperbaric oxygen therapy sessions were provided in a single-patient hyperbaric chamber at 1.2–1.6 ATA for 40 minutes. The status of the redox homeostasis system was assessed based on the data of the platinum electrode open circuit potential measured in blood plasma by using the potentiometric method; and the blood plasma antioxidant activity was assessed by cyclic voltammetry.Results. The analysis of the results showed that there was a direct relationship indicating the positive effect of hyperbaric oxygen therapy on the balance status of the pro- and antioxidant systems of the body, and on the improvement of blood counts.Conclusion. The early inclusion of hyperbaric oxygen therapy in the complex treatment of transplant patients with tumors of the reproductive system contributes to a more rapid recovery of pro- and antioxidant systems of the body, blood counts.